Development of the Educational Game Tool "Fun Mathematic Board" as a Numeracy Learning Medium for 5–6-Year-Old Children at Al Azhar Islamic Kindergarten Tulungagung - Agya, Badi Fadila Nur; Zainuddin , Mohammad; Wahyuni, Sri (Journal of Educational Sciences, 2025)
Teaching numeracy in early childhood significantly influences cognitive and academic development. Insufficient numeracy stimulation during the golden age may lead to future difficulties in learning mathematics and long-term life challenges. Early childhood education serves as a bridge to introduce foundational numeracy skills, making it essential to implement effective teaching strategies. A play-based approach using educational game media is an effective solution for numeracy learning in children aged 5–6 years. This research and development study produced the Fun Mathematic Board, an educational board game designed to enhance early numeracy skills. The game's feasibility was evaluated by game experts, subject matter experts, and users. The validation results showed that material experts rated it 89.06%, while game experts gave it 98.44%. The feasibility test results confirmed the game's suitability without revision, with a 93.1% approval rating in small-group trials and 91.5% in large-group trials. These findings highlight the Fun Mathematic Board as an effective tool for early numeracy learning.